Implementasi Dan Relevansi Sistem Komando Dalam Doktrin Een En Ondeelbaar Terhadap Penentuan Tuntutan Pidana Melalui Rencana Tuntutan Perkara Tindak Pidana Umum Pada Kejaksaan Negeri Yogyakarta - Hendratmoko, Vito; Permana, Wahyu Priyanka Nata (Fakultas Hukum Universitas Islam Indonesia, 2025)
This research is motivated by the implementation of the command system for determining criminal charges, which adopts the Een En Ondeelbaar Doctrine. While effective in ensuring uniformity, the limited understanding of the Head of the Prosecutor's Office regarding certain cases often leads to charges that do not align with legal facts presented in court. Based on this background, this research raises the following problems: How is the implementation of the charge plan concept for public prosecutors in determining criminal charges in general criminal cases at the Yogyakarta District Prosecutor's Office? and How is the relevance of the command system in the Een En Ondeelbaar Doctrine in influencing the consistency and uniformity of determining criminal charges in general criminal cases at the Yogyakarta District Prosecutor's Office?. This study uses an empirical legal research approach with a sociological approach. The findings indicate that the charge plan aims to ensure the independence of public prosecutors, but it often does not align with the facts presented in court because of the prosecution controller’s understanding of the cases, and the command system in the prosecution office influences the consistency and uniformity of criminal charges, reflecting a coordinated institutional policy.